An Overview of General Insurance Policy in India: Understanding General Insurance Policies in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Fire, floods, accidents, man-made disasters, and theft are all covered by general insurance for your house, travel, car, and health (non-life assets). Motor insurance, health insurance, travel insurance, and house insurance are all examples of general insurance. A general insurance policy compensates the insured for losses sustained throughout the policy's term. The purpose of this article is to provide an overview of general insurance policies in India.